2013
DOI: 10.1007/s00109-013-1116-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinin B1 receptor deficiency attenuates cisplatin-induced acute kidney injury by modulating immune cell migration

Abstract: Kinin B1 receptor is upregulated after cisplatin exposure. Kinin B1 receptor deficiency diminishes the nephrotoxicity caused by cisplatin. Kinin B1 receptor deficiency ameliorates the inflammatory response. Kinin B1 receptor deficiency diminishes apoptosis caused by cisplatin. Kinin B1 receptor antagonism ameliorates renal function after cisplatin injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…In fact, local IL-10 affects host immune response in many levels, including decrease in CD8 + T-cell-mediated tumor lysis, down regulation of major histocompatibility complex (MHC) class II and co-stimulatory molecules in dendritic cells 38 39 . Moreover, the kinin B1 receptor has been already associated with the migration of immune cells to injured tissues 40 . In our study, we observed that lungs from WT animals presented lower number of vessels compared to B1 receptor deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, local IL-10 affects host immune response in many levels, including decrease in CD8 + T-cell-mediated tumor lysis, down regulation of major histocompatibility complex (MHC) class II and co-stimulatory molecules in dendritic cells 38 39 . Moreover, the kinin B1 receptor has been already associated with the migration of immune cells to injured tissues 40 . In our study, we observed that lungs from WT animals presented lower number of vessels compared to B1 receptor deficient mice.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of macrophage infiltration promotes a functional and histological renal protection, indicating a pathogenic role of macrophages [5557] . Although no study has been conducted to identify the macrophage polarization in CN, several studies have indicated that macrophage infiltration is closely related to the pro-inflammatory cytokine release in the CN [58,59] . Therefore, it is presumable that these macrophages are M1 phenotype.…”
Section: Macrophage Polarization In Other Kidney Diseasesmentioning
confidence: 99%
“…Multiple pathways and molecules are involved in cisplatin-induced nephrotoxicity and apoptosis is observed after cisplatin administration [ 31 , 32 ]. Apoptosis may occur in cisplatin treatment by activation of apoptotic pathways, such as intrinsic mitochondrial pathway and extrinsic pathway activated by death receptors [ 1 , 33 , 34 ]. TNFR-2 mediates apoptosis in cisplatin-induced injury and is one of the death receptors of the extrinsic pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNFR-2 mediates apoptosis in cisplatin-induced injury and is one of the death receptors of the extrinsic pathway [ 35 ]. Moreover, the Bax/Bcl-2 ratio can be used to determine the intrinsic pathway of apoptosis [ 33 , 34 ]. Cisplatin treatment induced upregulation of TNFR- 2 and Bax/Bcl-2 ratio, while PPAR-α knockout mice are protected against this upregulation.…”
Section: Discussionmentioning
confidence: 99%